Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.3174/ajnr.a3610
|View full text |Cite
|
Sign up to set email alerts
|

CT Perfusion Can Predict Overexpression of CXCL8 (Interleukin-8) in Head and Neck Squamous Cell Carcinoma

Abstract: Background and Purpose Increased angiogenesis in head and neck squamous cell carcinoma correlates to more aggressive tumors with increased morbidity. As both elevated blood flow and high serum CXCL8 levels are correlated with increased angiogenesis, our objective was to see if elevated blood flow measured with CT perfusion correlated with CXCL8 levels, thereby helping to identify candidates for targeted therapies that inhibit the Bcl-2 proangiogenic pathway associated with CXCL8. Materials and Methods After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Several studies have determined BF, BV, PS, and MTT values in malignant SCCs of head and neck region: Tawfik et al, 10 Faggioni et al, 3 Trojanowska et al, 11 and Jo et al 12 The main reason for variability in CTp parameters in these studies is due to use of different postprocessing software provided by different vendors. 13 It is also believed that acquisition factors—tube potential, tube current, total scan time, and scan interval—all play a role in determination of perfusion parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have determined BF, BV, PS, and MTT values in malignant SCCs of head and neck region: Tawfik et al, 10 Faggioni et al, 3 Trojanowska et al, 11 and Jo et al 12 The main reason for variability in CTp parameters in these studies is due to use of different postprocessing software provided by different vendors. 13 It is also believed that acquisition factors—tube potential, tube current, total scan time, and scan interval—all play a role in determination of perfusion parameters.…”
Section: Discussionmentioning
confidence: 99%
“…We observe the downregulation of other DEGs c-Met, RAS, ERK, Elk1 and STAT3 that could affect the VEGFA dependent angiogenesis 52 . The upregulated DEGs ITFRSF25, TNFRSF4, CCL23, CCL26, and CX3CL1 of cytokine-cytokine interaction pathway is reportedly activating PI3K/AKT pathway 5559 , which in turn induces the angiogenesis through activating mTOR 54 and NFKB pathway 60 . The upregulated DEGs IL18RAP and CXCL1has shown to modulates the NFKB and thus induces the angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It is already known that elevated blood flow on CTP is correlated with angiogenesis, microvessel density (MVD) and increased tumor vascularity, and is has been found to be correlated with tumor recurrence and the tumor’s ability to metastasize also in HNSCC [ 6 , 7 , 12 ]. Several studies also investigated the ability of CTP to predict therapy success in HNSCC and it was found that patients with decreased perfusion showed higher local recurrences [ 13 ] and higher perfusion (BV and BF) correlated with improved chemotherapy response [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that CTP has a positive correlation with microvessel density and can therefore partly reflect neo-angiogenesis in tumors. Furthermore, prognostic impact has been found in several studies evaluating CTP in head and neck cancer as well as in other tumor entities [ 1 , 4 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation